Evaluasi Proses Bisnis Sistem Informasi Kebutuhan Pelatihan (SIBULAT) Badan Pengembangan Dan Pemberdayaan Sumber Daya Manusia Kesehatan (BPPSDMK) Dengan Menerapkan Process Mining Dan Quality Evaluation Framework (QEF) - Muhamad Fauziawan Agung Rewanda; Nanang Yudi Setiawan; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
BPPSDMK is one of the departments within the auspices of the Ministry of Health of the Republic of Indonesia and in the execution of its duties, the responsible accountable directly to the Minister of Health. BPPSDMK have a responsibility in developing and empowerment of existing human resources in the ministry of health. BPPSDMK has had 21 applications one is Information Systems Training Needs (SIBULAT). At this time, in SIBULAT yet there is a Standard OperationaI Procedure (SOP) written so that the evaluation of the performance of the system can be more difficult to do and causes the plot to be irregular according to the schedule and can change at any time.. By therefore, therefore, research needs to be done with how to identify the business processes contained in the BPPSDMK, create a business process model and conduct an evaluation of the business process SIBULAT in order to facilitate the evaluation process and in the future SIBULAT have better business processes as well as efficient. Interview Data and eventlog is used in the evaluation process as a source of data, then the data will be processed using the methods of process mining and proceed with the analysis using the tool help Disco and ProM 6 Tools. After that, the method of Quality Evaluation Framework (QEF) is used to perform a follow-up evaluation. In this method the comparison is done between the target value with the value from the results of the interview as well as the value of the eventlog. 7 quality factor obtained from the output evaIuasi that has been done, with the results of the calculations show that there are 4 quality factor that is not in accordance with the target which means that the processing time recorded in the eventlog exceed predetermined targets.